Influence of sweep interference on satellite navigation time-domain anti-jamming - Li, Baiyu; Qiao, Jia; Lu, Zukun; Yu, Xiaoyou; Song, Jie; Lin, Baojun; Li, Xianghao (Frontiers in Physics, 2023)
The global navigation satellite system (GNSS), which is represented by global positioning systems (GPS), is widely used in various civil and military fields and represents an important basis for space-time information services. However, the frequency bands of satellite navigation signals and some radar signals partially overlap, and the radar’s strong signal power seriously affects the normal reception of weak satellite navigation signal power. To further improve anti-jamming with sweep interference in the time domain, this paper focuses on the swept-frequency interference scenario, studies the influence of the swept-frequency interference on time-domain-adaptive anti-jamming, and proposes a timing reset based on the adaptive filter. The repair method can effectively deal with the influence of the swept-frequency on time-domain-adaptive anti-jamming and can suppress interference and protect signals at the same time. Simulation experiments verify the effectiveness of the anti-jamming method proposed in this paper. Under the conditions of typical simulation scenarios, using the method in this paper, the influence time of the frequency sweep interference on the navigation signal is less than 1ms, which is greatly reduced compared to traditional methods. The proposed anti-jamming method is of great significance for improving the survivability of satellite navigation receivers in swept-frequency interference scenarios.